Developing english supplementary book in teaching speaking skill used visio media for 7 grade at MTs Syekh Subakir - Fathiah Salma; Ahmad Saifudin; Siti Rofi’ah (Patria Educational Journal (PEJ), 2023)
Abstract: The purpose of this study was to determine the results of validator validation and student responses to the product that the researcher had developed in the form of a supplementary book with a combination of Visio media to test 16 7B grade students. MTs Syekh Subakir 1. This study uses Research and Development (R&D) used Borg and Gall theory (2003). The material presented in the media is descriptive text and this additional product focuses on speaking skill. Data collection technique were carried out used unstructured interviews and surveys. The instruments used are interview guidelines and questionnaires used a Likert scale. Based on the results of the validation carried out by material and media experts, from the results of student responses, the percentage of results obtained were 82,3%, 83,3%, and 79.8% with the criteria "Good or Valid or useful". so, it can be concluded that additional descriptive text books as learned media are very well used in the English learned process.